The Influence Of The Loan-To-Deposit Ratio On The Return On Assets In Banking Companies Listed On The Indonesian Stock Exchange During The Period 2015-2019 - Maghfuriyah, Alfi; Permatasari, Ayu Intan; Nurjaya; Setiawan, Teddy (Neo Journal of economy and social humanities, 2023)
In this study, the impact of the Loan to Deposit Ratio (LDR) on Return on Assets (ROA) in banks listed on the Indonesia Stock Exchange from 2015 to 2019 is to be examined. The information used in this study is secondary information. Three companies were collected as research samples after the sample was chosen using a purposive sampling technique from banking data obtained at the Indonesia Stock Exchange over a five-year period. Using documentation as a data collection tool. The traditional assumption test and the simple linear regression test are the analysis methods employed. The Pearson product moment correlation study indicates that the LDR and ROA have a positive and significant association, with a result of 0.748. While the results of simple linear regression analysis show a coefficient of determination (r2) of 0.560, this study's regression model can only account for 56% of the relationship between the independent variable LDR and the dependent variable ROA; the remaining 44% is determined by independent factors or variables unrelated to the study.